Penatalaksanaan Fisioterapi Pada Kasus DropHand Dextra E.C Lesi Saraf Radialis Di Rs PkuMuhammadiyah Yogyakarta - Arifiana, Riski; , Agus Widodo, S.Fis, M.Kes (2016)
THE IMPLEMENTATION OF PHYSIOTHERAPY ON THE CASE OF DROP HAND DEXTRA CAUSED BY RADIALIS NERVOUS LESION AT RS PKU MUHAMMADIYAH YOGYAKARTA (Riski Arifiana, 2016, 42 pages) Background : Drop Hand is a symptom from radial nerve disorder that causes paralysis, which can cause weakness of the fingers, extensor muscles hands, and wrists hand. Purpose : To study about physiotherapy management in reducing pain, increase muscle strength, increasing range of motion in the case of Drop Hand using modalities infra red (IR), Faradic, and Therapeutic Exercise (TL). Results : After therapy for about six times the obtained results of the assessment of pain for silent pain T1 : 1 to be T6 : 1, motion pain T1 : 1 to be T6 : 1, press pain T1 : 3 to be T6 : 2, increase range of motion S : T1 : 300 - 00 - 400; S : T6 : 600 - 00 - 600, F : T1 : 180 - 00 - 250; F : T1 : 200 - 00 - 300, an increase in dorsal flexion wrist muscle strength T1 : 3-; T6 : 3, palmar flexion wrist T1 : 3-; T6 : 3, ulnar deviation T1: 3; T6 : 4, radial deviation T1 : 3; T6 : 4. Conclusion: Infra Red (IR), Faradic, dan Therapeutic Exercise (TL) can reduce pain caused by Drop Hand, can improve range of motion, and can increase muscle strength in the case of Drop Hand. Key word : Drop hand, Infra Red (IR), Faradic, and Therapeutic Exercise (TL).